2004
DOI: 10.1677/joe.1.05448
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype on the differential ontogeny of uncoupling protein 2 and 3 in subcutaneous adipose tissue and muscle in neonatal pigs

Abstract: The present study aimed to determine whether porcine genotype and/or postnatal age influenced mRNA abundance or protein expression of uncoupling protein (UCP)2 or 3 in subcutaneous adipose tissue (AT) and skeletal muscle (SM) and the extent to which these differences are associated with breed-specific discordance in endocrine and metabolic profiles. Piglets from commercial and Meishan litters were ranked according to birth weight. Tissue samples were obtained from the three median piglets from each litter on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 43 publications
2
28
1
Order By: Relevance
“…Interestingly, the differences observed in plasma T 3 between Meishan and commercial piglets on day 0 in a previous study (Mostyn et al 2004) were not apparent. A potential reason for this disparity was that the maternal diet was different in the present study.…”
Section: Thyroid Hormones In Sows Milkmentioning
confidence: 60%
See 2 more Smart Citations
“…Interestingly, the differences observed in plasma T 3 between Meishan and commercial piglets on day 0 in a previous study (Mostyn et al 2004) were not apparent. A potential reason for this disparity was that the maternal diet was different in the present study.…”
Section: Thyroid Hormones In Sows Milkmentioning
confidence: 60%
“…Milk was manually sampled from each sow and immediately frozen at K20 8C. On days 0 and 4, morphometric measurements, including head circumference and crown to rump length (CRL), were made along with the measurement of total body electrical conductivity (TOBEC) as described previously (Mostyn et al 2004). This is a non-invasive technique designed to estimate fatfree mass and thereby indirectly measures body fat in live animals (Bellinger & Williams 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, physiological studies have shown that porcine genotype must be taken into consideration when selecting an appropriate model because despite the minipig being smaller, it possesses more fat (0.117 to 0.158 kg fat for a 1.25 kg 5-day old neonatal piglet, (Sheng et al, 1988)) compared with modern domestic breeds (0.03 kg fat for a 1.5 kg 1 day old neonatal piglet, Shields et al, 1983)) and exhibits altered uncoupling protein (UCP) expression and endocrine profile at birth compared with modern domestic breeds of pigs (Knol et al, 2002;Mostyn et al, 2004Mostyn et al, , 2006. Compromised UCP abundance in adipose tissue may contribute to excess fat deposition in later life resulting in obesity, hence providing a natural model for obesity (Dyson et al, 2006).…”
Section: Litten-brown Corson and Clarkementioning
confidence: 99%
“…However, an air of caution must be taken if using these porcine growth curves as data were collected only for a specific domestic breed combination (i.e. Large White X Landrace), reared under standard commercial conditions, not experimental conditions; it is known that growth and development varies between porcine genotypes (Mostyn et al, 2004) and also under different management regimes (Kusec et al, 2007).…”
Section: Litten-brown Corson and Clarkementioning
confidence: 99%